2020
DOI: 10.1104/pp.20.00439
|View full text |Cite
|
Sign up to set email alerts
|

The Histone-Modifying Complex PWR/HOS15/HD2C Epigenetically Regulates Cold Tolerance

Abstract: Cold stress is a major environmental stress that severely affects plant growth and crop productivity. Arabidopsis (Arabidopsis thaliana) HIGH EXPRESSION OF OSMOTICALLY RESPONSIVE GENE15 (HOS15) is a substrate receptor of the CULLIN4based CLR4 ubiquitin E3 ligase complex, which epigenetically regulates cold tolerance by degrading HISTONE DEACETYLASE2C (HD2C) to switch from repressive to permissive chromatin structure in response to cold stress. In this study, we characterized a HOS15-binding protein, POWERDRESS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 50 publications
0
44
0
Order By: Relevance
“…Consistently, the deposition of histone acetylation on these genes was increased in the P6 overexpression lines than in the wild-type ( Figure 6 c). Previous reports had demonstrated that HD2C was involved in many abiotic stresses like salt, heat, and cold stress [ 19 , 21 , 56 ]. Therefore, further studies are needed to investigate how CaMV facilitates the hosts to survive these stresses through histone deacetylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, the deposition of histone acetylation on these genes was increased in the P6 overexpression lines than in the wild-type ( Figure 6 c). Previous reports had demonstrated that HD2C was involved in many abiotic stresses like salt, heat, and cold stress [ 19 , 21 , 56 ]. Therefore, further studies are needed to investigate how CaMV facilitates the hosts to survive these stresses through histone deacetylation.…”
Section: Discussionmentioning
confidence: 99%
“…In response to heat stress, HD2C was proved to regulate heat-responsive genes by physically cooperating with chromatin remodeling complex like SWI/SNF [ 19 ]. HD2C had also been identified as a core factor in chromatin structure switching from repressed to active status in response to cold stress, whose degradation was facilitated by interacting with HOS15, a substrate receptor of CULLIN4 (CUL4) -based E3 ubiquitin ligase complex, under cold stress [ 20 , 21 , 22 ]. Although the function of HD2C in abiotic stress was extensively studied, its functions in biotic stress have remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The histone deacetylase inhibitor Trichostatin A and DNA methylation inhibitor 5-Aza-2′-Deoxycytidine alter the expression of cold-induced genes in Arabidopsis thaliana, enhancing its cold tolerance [ 44 ], and in response to cold stress, histone H3 acetylation-mediated chromatin remodeling is necessary for transcriptional activation of a cold-inducible rice gene, OsDREB1b [ 45 ]. The POWERDRESS (PWR)-HOS15-HD2C complex in Arabidopsis negatively regulates the expression of COR genes through H3 deacetylation and repressive chromatin structure [ 25 , 46 ], whereas the histone deacetylase HD2C is degraded by the PWR-HOS15 complex, resulting in transcriptional activation of COR genes ( RD29A and COR15A / 47 / 78 ) under cold stress, by facilitating H3 acetylation and the permissive chromatin structure. In cold-treated banana ( Musa acuminata ) fruits, the increased levels of H3 and H4 acetylation in the promoters of ω-3 fatty acid desaturase genes ( MaFADs ) are correlated with the enhanced transcription of ω-3 MaFADs ; the MaMYB4 transcription factor negatively regulates the transcription of ω-3 MaFADs by recruiting the histone deacetylase MaHDA2 [ 47 ].…”
Section: Chromatin Dynamics Associated With Abiotic Stress-inducedmentioning
confidence: 99%
“…Similarly, the rice AGO2 is associated with the enhanced H3K4me3 and the reduced H3K27me3 levels of the BG3 gene to facilitate its expression under salinity stress through chromatin modifications [ 75 ]. The PWR proteins also constitute a chromatin-remodeling complex with either HOS15 and HD2C, or HDA9 and ABI4 to repress the cold-responsive RD29A and COR15A / 47 / 78 or the drought-responsive CYP707A1/2 genes, respectively in Arabidopsis [ 46 , 87 ]. In addition, histone modifiers and transcription regulators together coordinate chromatin dynamics and gene expression, allowing alternative nucleosome configurations at transcription sites [ 10 , 11 , 12 , 13 ].…”
Section: Interplay Of Histone Modifications Chromatin Remodelingmentioning
confidence: 99%
“…Study demonstrated that HOS15 acts as a DCAF protein and interacts with and degrades the HD2C protein via ubiquitination and proteasome-mediated degradation, thus modulating the expression of cold-responsive (COR) genes under freezing stress in Arabidopsis (Park, et al 2018). Lim, et al (2020) studied the function of the HOS15 binding protein, POWERDRESS (PWR) in response to cold stress. This study showed that HOS15 interacts with HD2C with the help of PWR at the promoter region of COR genes, thus mediating the degradation of HD2C, leading to the upregulation of COR genes as a part of the cold stress response.…”
Section: Biological Functions Of Hd2 Family Members In Response To Environmental Stressesmentioning
confidence: 99%